Aggravation of excessive daytime sleepiness concurrent with aggravation of an injured ascending reticular activating system in a patient with mild traumatic brain injury: A case report. Issue 4 (January 2017) - Jang, Sung Ho; Kwon, Hyeok Gyu
Abstract: Background: We report on a patient who developed aggravation of excessive daytime sleepiness (EDS) concurrent with aggravation of an injured ascending reticular activating system (ARAS) following mild traumatic brain injury (TBI), demonstrated by follow-up diffusion tensor tractographies (DTTs). Methods: A 42-year-old male patient experienced head trauma resulting from flexion-hyperextension injury after collision with another vehicle from behind while stopped at an intersection. The patient lost consciousness for approximately 10 seconds and experienced no post-traumatic amnesia following the accident. The patient's Glasgow Coma Scale score was 15. No specific lesion was observed on the conventional brain MRI performed at 10 weeks after onset. The patient complained of EDS after the head trauma and aggravation of EDS with passage of time. The Epworth Sleepiness Scale indicated abnormality with a score of 12 at 10 weeks after onset (cut-off: 10 points full mark: 24 score) and it was aggravated with a score of 18 at 16 months. Results: On 10-week DTT, decreased neural connectivity of the intralaminar thalamic nucleus to the prefrontal cortex and basal forebrain was observed in both hemispheres. However, no significant abnormality was observed in the dorsal and ventral lower ARAS. On 16-month DTT, the upper portion of the left dorsal lower ARAS showed partial tearing and the ventral lower ARAS showed thinning (both sides) and partial tearing (right side). Conclusions: Aggravation of EDS concurrent with aggravation of an injured ARAS was demonstrated in a patient with mild TBI using DTT.